Is TKA femoral implant stability improved by pressure applied cement?: a comparison of 2 cementing techniques - Schonhoff, Mareike; Beckmann, Nicholas A.; Schwarze, Martin; Eissler, Marvin; Kretzer, Jan Philippe; Renkawitz, Tobias; Jäger, Sebastian (BMC musculoskeletal disorders, 2023)
The majority of knee endoprostheses are cemented. In an earlier study the effects of different cementing techniques on cement penetration were evaluated using a Sawbone model. In this study we used a human cadaver model to study the effect of different cementing techniques on relative motion between the implant and the femoral shaft component under dynamic loading.
Gesehen am 28.02.2023